Mothering – a mode of protecting rather than parenting in the aftermath of post separation family violence in Australia. (5th June 2020) - Francia, Leanne; Millear, Prudence; Sharman, Rachael
Abstract: The focus of this qualitative study was on separated mother's ( N = 36) lived experiences of mothering in the context of post separation family violence and the Australian family law system. Thematic analysis of interviews was guided by a theoretical framework, this being the Three Planets Model. Analysis of the data resulted in two themes relating to mothering being identified. Firstly, that women demonstrated a mode of protecting rather than parenting indicating that mothering was often undertaken in isolation and fear, within an adversarial family law system, and in the presence of a perpetrator of family violence. The second theme related to the aftermath of separation and the long dark shadow cast by family violence. After having left a controlling and violent relationship, separated mothers reported that there was no opportunity to recover, nor to healthily extricate themselves from family violence, which resulted in cumulative harm not only for their wellbeing but also for their children.